(untitled) (Comparative & International Education Series, 2022)
It was March 2005. After taking two connecting flights through the crowded London and Los Angeles, my flight touched down at the snow-covered Fairbanks International Airport, Alaska. It is often said, March is when Alaskans begin to embrace the winter season. The scenery, mountains, and rivers blanketed with snow were stunning. It was a dream come true, and only later I realized Alaska has been a draw for dreamers and adventurers as it is well-known for solitude and outdoors.